Analysis of Dynamic Governance in the Implementation of Hajj at the Office of the Ministry of Religious Affairs of Blitar Regency - Dwi Ayu Damayanti; Slamet Muchsin; Hayat Hayat (Eduvest - Journal of Universal Studies, 2025)
The hajj pilgrimage process at the Office of the Ministry of Religion of Blitar Regency has been marked by an increasing waiting period each year, leading to longer queues. This study aims to: 1) assess the implementation of the hajj service policy at the Office of the Ministry of Religion of Blitar Regency; 2) analyze the dynamics of governance in the execution of hajj services; and 3) identify both supporting and inhibiting factors affecting the policy's effectiveness in enhancing service quality. Employing a qualitative and descriptive research approach, the study finds that policy implementation dimensions—Communication, Resources, Disposition, and Bureaucratic Structure—are generally functioning well. However, the resource dimension requires improvement for optimal service delivery. The Dynamic Governance analysis reveals that the Office of the Ministry of Religion of Blitar Regency, through its Thinking Forward initiative, has effectively synergized with the Ministry of Religion of the Republic of Indonesia. Strategic policies have been adopted to manage the hajj waiting period more efficiently. Innovations such as bio visa recording have been implemented independently by the Blitar office, bypassing the Central Ministry. Furthermore, the Blitar office is working to increase pilgrimage capacity by exceeding standard quotas and engaging in comparative studies with Tangerang City to adopt best practices. Overall, while improvements have been made, ongoing enhancements in resource management and strategic policy implementation are essential for better handling of the hajj waiting period and service quality.